Description of two new species of Nelphe Herrich-Schäffer, with comments on the genus (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina) - Pinheiro, Lívia R. (Zootaxa, 2016)
Two new species of Ctenuchina are described from Haiti and Dominica, respectively: Nelphe trimaculata Pinheiro, sp. nov., and N. dominica Pinheiro, sp. nov. Nelphe trimaculata differs from all other species of Nelphe in the three linear (as opposed to round) dark brown markings on cell CuP-1A and on the inner margin of the forewings. Nelphe dominica differs from other species placed in Nelphe in the sixth and seventh abdominal tergites, with orange scales covering not only the lateral surfaces of the tergites as it occurs in other species, but also the dorsal surface. Both new taxa are illustrated in habitus and genitalia, and comments on the genus, now with 13 valid species, are provided.